The Childfree Phenomenon among Indonesian Artists: A Tarbawi Tafsir Perspective on Progeny - Umi Waheeda; Abdul Aziz; Lukman Hakim (ZAD Al-Mufassirin, 2026)
The childfree phenomenon among Indonesian celebrities has sparked intense public debate regarding the essence of family and reproductive purposes. This research is crucial as this trend potentially shifts the paradigm of value education within Muslim families in Indonesia. This study aims to analyze the childfree phenomenon through the lens of Tafsir Tarbawi to uncover the educational values inherent in the concept of progeny (dzurriyat). Utilizing a descriptive qualitative method with a library research approach, this study analytically examines Quranic verses concerning offspring thematically. The findings indicate that from a Tarbawi perspective, progeny is not merely a biological aspect but an educational mandate for the continuity of monotheistic messages (risalah tawhid). The discussion highlights that the childfree choice among celebrities is often driven by psychological anxiety and materialism, which contradicts the values of raja’ (hope) and tawakkal (trust in God). The novelty of this research lies in its integration of modern lifestyle discourse with Quranic educational values that position children as subjects of hereafter investment. The implications of this study emphasize the need for a comprehensive reorientation of pre-marital education curricula to safeguard family values against the influence of secular lifestyles.